Crowdfunding: An Emerging Source of Raising Funds In Nigeria - Aladejebi, Olufemi (Archives of Business Research, 2020)
Crowdfunding has become a new phenomenon of raising capital for business. Crowdfunding is prevalent in developed nations, while it is just getting popular in developing countries. The research method used for the research was multiple case studies. The purposive sampling method was used to select the five participants for the research. The questionnaire contained fifteen questions. Eighteen themes were generated from the questions. As a result of Social distancing for protection under COVID 19, questions were sent to the respondents via the Google form. The thematic analysis result revealed that agricultural business is the most popular when it comes to crowdfunding. It is an opportunity for entrepreneurs to raise money from another source, easier to access funds through crowdfunding. The crowdfunding approaches used to raise funds by the five participants are loans, hybrid, reward-based, and royalty-based approaches. Crowdfunding is an effective funding alternative for entrepreneurs.